(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This research paper analyzes the tourism cluster of Uzbekistan. It describes its strengths and weaknesses, as well as the factors that affect its efficiency. The paper proposes ways to optimize the tourism cluster, including the development of tourism infrastructure, improving the quality of tourist services, expanding the range of tourist offers, promoting the tourism potential of Uzbekistan on the world market, and state support for tourism development. The conclusion is that the tourism cluster of Uzbekistan has great potential for development. With the implementation of the proposed measures, Uzbekistan can become one of the leading tourist destinations in the world.